Technical report: mathematical analysis of crash sensor using spring mass model / Siti Khalijah Ab Ghani, Nor Hidayu Kamaruzaman and Noor Izzati Fatin Muhammad Azif - Ab Ghani, Siti Khalijah; Kamaruzaman, Nor Hidayu; Muhammad Azif, Noor Izzati Fatin (2017)
In this project, mathematical analysis of crash sensor using spring mass model is presented. Laplace Transform method is used to derive the equation for displacement of beams from vibration equation. This project includes three types of material (steel, copper, and aluminium) with two different dimension of cantilever beam. From that, we will know the maximum response of beams so that we can conclude the best dimension of sensor to trigger airbag which is length=0.45m, breadth= 0.02m, and depth= 0.003m.